Interaction of bacteriophage P1 with an epiphytic Pantoea agglomerans strain—the role of the interplay between various mobilome elements - Giermasińska-Buczek, Katarzyna; Gawor, Jan; Stefańczyk, Emil; Gągała, Urszula; Żuchniewicz, Karolina; Rekosz-Burlaga, Hanna; Gromadka, Robert; Łobocka, Małgorzata (Frontiers in Microbiology, 2024)
P1 is a model, temperate bacteriophage of 94-kb genome. It can lysogenize representatives of the Enterobacterales order. In lysogens, it is maintained as a plasmid. We tested P1 interaction with the biocontrol P. agglomerans L15 strain to explore the utility of P1 in P. agglomerans genome engineering. A P1 derivative carrying the Tn9 (cmR) transposon could transfer a plasmid from Escherichia coli to the L15 cells. The L15 cells infected with this derivative formed chloramphenicol-resistant colonies. They could grow in liquid medium with chloramphenicol, only after adaptation, and did not contain prophage P1 but the chromosomally inserted cmR marker of P1 Tn9 (cat). The insertions were accompanied by various rearrangements upstream of the Tn9 cat gene promoter and the loss of IS1 (IS1L) from the corresponding region. Sequence analysis of the L15 strain genome revealed a chromosome and three plasmids of 0,58, 0,18 and 0,07 Mb. The largest and the smallest plasmid appeared to be partitionally and replicationally incompatible with prophage P1, respectively. In the L15 derivatives cured of the largest plasmid, P1 with Tn9 could not replace the smallest plasmid even if selected. However, it could replace the smallest as well as the largest plasmid of L15 if only its Tn9 IS1L sequence driving the Tn9 mobility was inactivated or if it was enriched with an immobile kanamycin resistance marker. Moreover, it could develop lytically in the L15 derivatives cured of both these plasmids. Clearly, under conditions of selection for P1, the mobility of P1 selective marker determines whether or not the incoming P1 can outcompete the incompatible L15 resident plasmids. Our results demonstrate that P. agglomerans can serve as a host for bacteriophage P1 and can be engineered with the help of this phage. They also provide an example of how antibiotics can modify the outcome of horizontal gene transfer in natural environments. By prediction, numerous plasmids of Pantoea strains contain determinants of replication or partition incompatibility with P1. Thus, P1 with an immobile selective marker may be a tool of choice in curing these strains from the respective plasmids to facilitate their functional analysis.